Carbon dots as a sustainable electrolyte enhancer in aqueous alkaline electrochemical capacitors - Ganesh, Gayathry; Sunil, Vaishak; Ling, JinKiong; Qamar, Ummiya; Izan Izwan, Misnon; Kuila, Biplab Kumar; Das, Santanu; Yang, Chun-Chen; Jose, Rajan (Elsevier Ltd, 2024)
In the endeavour to increase the energy density and to widen the potential window of aqueous alkaline electrochemical capacitors (EC), this study explores the role of carbon dots (CDs) as an additive in potassium hydroxide electrolyte. The CDs with an average size of ∼2.2 nm and negative surface potential are synthesized from a dispersion of palm kernel shell powder in water using a low-temperature hydrothermal process. Electrochemical measurements show that the CD–electrolyte ion (K+) interaction has improved counter ion adsorption in porous carbon electrodes via lowering the characteristic resistances and time constants, which significantly improved the fraction of adsorbed charges than diffusively stored. The improved ionic conductivity is attributed to the improved wettability introduced by the hydrophilic functional groups in the CDs. These parametric changes widened the potential window and marked an 80 % increase in the specific energy and over a 10 % increase in specific power in a practical EC with similar mass-loading as commercial devices. The device with CDs demonstrated superior cycling stability and Coulombic efficiency than the control device without them. These findings underscore the potential of CDs as a promising avenue for advancing the performance parameters of aqueous electrolyte EC, aligning with the overarching goal of realising economical, environmentally friendly, and sustainable energy storage solutions.